MENINGKATKAN MINAT DAN HASIL BELAJAR APRESIASI TARI BERPASANGAN NUSANTARA MELALUI MEDIA AUDIOVISUAL PADA SISWA KELAS 8ASMP NEGERI 3 PETARUKAN - Suharwati, Eni (Jurnal Penelitian Pendidikan, 2014)
The study was conducted as a classroom action researchdue to students lack of interest in art and culture subject, especially dancing. This is shown by the students test results which are mostly still below the minimum passing grade criteria.Based on that observations, this research aims to study students’ interest in art appreciation subject, particularly pair-dancing,and their learning outcomes using audio-visual media. The method used in this study is classroom action research method using cycle stages, the first cycle and second cycle used the audio-visual media. The research result shows that there is improvements in student interest in learning the national dance, as evidenced by the attention and enthusiasm of students in the learning process, as well as improvements in their learning outcomes. On the pre cycle the total number of students who scored above 75 were only 42,50%, then it reached 85% by the end of the second cycle. Based on the above research results, the recommendations are : (1) specifically for art and culture teachers, this method can be used in the learning process to improve students interest, particularly in practicing pair-dancing; (2) for teachers in general, they should always improve their knowledge, abilities, skills, and creativity in order to improve the learning process so that the process is meaningful and fun for students; (3) schools should also be able to facilitate the teacher to use instructional media in teaching and learning activities.